(3JYde (BMicrosoft Office Excel 2010s ((3GdbGgQIs (3Hj Sj dGHs, 2010)
(3jYJHQ HQfGeL (Bmicrosoft excel 2010 (3ef Cbhi GdHQGeL GdJj JSJNOe dYed GdYOjO ef GdegGe hGdhXGFa eKd JfXje hJNRjf GdHjGfGJ hYed GdMSGHGJ GdHSjWI hGdeYbOI hJMdjd hLOhdI GdHjGfGJ eY GdQSe GdHjGfj hJfSjb hJMVjQ GdJbGQjQs
Keywords: excel 2010 -- (3JYdjes -- (3ehGO SeYjI hHUQjIs; (3GdHQeL GdEdcJQhfjIs -- (3JYdjes -- (3ehGO SeYjI hHUQjIs; (3GdMGSHGJ GdEdcJQhfjIs -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjG cHGQs -- (3ehGO SeYjI hHUQjIs